HEALTH LEVEL ASSESSMENT OF PT ALLO BANK INDONESIA TBK FOR THE PERIOD 2020-2024 - Ana Dwi Pertiwi (Asosiasi Dosen Muda Indonesia, 2026)
The financial performance of an entity serves as a measure used to assess a company's ability to generate revenue or profits reflected in a given period. One of the digital banks in Indonesia is Allo Bank. The purpose of this research is to provide an analysis of how the assessment of the health level of PT Allo Bank Indonesia Tbk for the 2020-2024 period uses eight variables, namely NPL, LDR, GCG, ROA, ROE, NIM, BOPO, and CAR. The analysis technique applied in this study is to analyze financial statements through the RGEC approach. The results of this study show that overall, during the period 2020 to 2024, Allo Bank's health condition received a Very Healthy rating in 2020 and 2021, with composite values of 87.50% and 90%, respectively. And obtained the Healthy rating for the 2022-2024 period with a composite value of 80%, 82.50%, and 82.50%, respectively.